THE IMPLEMENTATION OF PROJECT BASED LEARNING MODEL USING CONCRETE MEDIA IN IMPROVING NATURAL SCIENCE LEARNING AT THE FOURTH GRADE STUDENTS OF SDN PUCUNG KIDUL 03 IN THE ACADEMIC YEAR OF 2014/2015 - Konita, Ardiana Pangestika (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Implementation of Project Based Learning Model Using Concrete Media in Improving Natural Science Learning At The Fourth Grade Students Of SDN Pucung Kidul 03 in The Academic Year Of 2014/2015. The purpose of the study was to improve the teaching learning process of natural science in grade IV through project based learning model using concrete media. This study was a collaborative classroom action research in three cycles consisting the following steps planning, implementation, observation and reflection. The subject of the study was 31 students of grade IV SDN Pucung Kidul 03. The result of the study showed that the use of project based learning model using concrete media improved the teaching learning process of natural science in grade IV SDN Pucung Kidul 03 academic year of 2014/2015.Keywords: Project Based Learning, Concrete Media, Natural Science